Diseño de una central fotovoltaica para abastecer la demanda de energía eléctrica a la granja avícola “Villa” ubicada en la Latacunga parroquia Juan Montalvo barrio San José. - Lema Escobar, Alexander Fabricio (2021)
The electricity generated by photovoltaic solar panels is very important because it is unlimited and does not pollute, it helps producers who have businesses in rural areas to have their own source of energy. This generation plant can be provided by natural sources and is used in two different ways, one of the ways to use it is to sell to the network, while the other can be consumed directly. At present it is very important to integrate renewable natural resources, since climate change may be on our planet to provide energy, incorporating a renewable source that helps us supply the loads and thus reduces the need to use other non-renewable energy sources. . The installation of a photovoltaic plant is favorable for the environment since it does not influence factors of damage to human, animal and plant health. The only argument that can be against these facilities is the amount of land that must be occupied for their facilities. However, this is not a real inconvenience for the installation of this type of generation plants. 4 This research seeks to carry out a feasibility study for the conceptual design of a photovoltaic plant that allows the supply of electricity to producers and residents, especially in rural or remote areas where power lines cannot be reached or it is very difficult to achieve it.